Pengaruh pemberian MP-ASI program dan MP-ASI komersial terhadap pertumbuhan bayi usia 6-11 bulan di Kabupaten Kampar - Dedy Rochyani; Muhammad Juffrie; I Made Alit Gunawan (Jurnal Gizi Klinik Indonesia, 2007)
Background: Growth alteration in 6-11 months old baby occurred due to inappropriate practice in complementary food consumption (complementary breastfeeding). Quality and quantity deficit of household complementary breastfeeding products could cause serious problems in baby growth. One of the alternative solution was consuming complementary breastfeeding from industrial products. Consuming complementary breastfeeding blended food (program complementary breastfeeding) for 6-11 months old babies in Medan tended to show no relationship with their nutritional status based on Z-score index weight for age. One of the possible reason was low level acceptance of program complementary breastfeeding in 2003.Objective: To determine the level of acceptance of both program and commercial complementary breastfeeding with their relationship toward 6-11 months old baby growth in sub urban poor families in Kampar Sub District.Method: Quasi experimental design was conducted. Purposive technique sampling was chosen and samples were divided into two groups that received different intervention. The first group that received program complementary breastfeeding consisted of 54 babies and the second group that received commercial complementary breastfeeding consisted of 46 babies of 6-8 months old babies from sub urban poor families. Data obtained was analyzed with univariate, bivariate, and multivariate analysis.Results: Level of acceptance of commercial complementary breastfeeding was higher than program complementary breastfeeding for 6-11 months old babies in sub urban poor families in Kampar Sub District (p=0.038). These babies had a significant additional in weight and  after consuming program and commercial complementary breastfeeding (p<0.001). Weight gain for the group that given commercial complementary breastfeeding was higher than that for the group that given program complementary breastfeeding (p<0.001), while body length also added during three months treatment but not significant (p>0.05).Conclusion: Consumption of program and commercial complementary breastfeeding could increase the weight gain and body length significantly.